Biomechanics: an integral part of sport science and sport medicine - Elliott, B. (Journal of Science and Medicine in Sport, 1999)
Biomechanics is one of the disciplines in the field of Human Movement and Exercise Science and it can be divided into three broad categories from a research perspective. Clinical biomechanics involves research in the areas of gait, neuromuscular control, tissue mechanics, and movement evaluation during rehabilitation from either injury or disease. Occupational biomechanics typically involves research in the areas of ergonomics and human growth or morphology as they influence movement. While these two categories will briefly be discussed, the primary aim of this paper is to show the role of biomechanics in sports science and sports medicine. Research in sports biomechanics may take the form of describing movement from a performance enhancement (such as matching of impulse curves in rowing) or injury reduction perspective (such as diving in swimming or the assessment of knee joint loading during downhill walking). However, the strength of sports biomechanics research is the ability to establish an understanding of causal mechanisms for selected movements (such as the role of internal rotation of the upper arm in hitting or striking, and the influence of elastic energy and muscle pre-stretch in stretch-shorten-cycle actions). The growth of modelling and computer simulation has further enhanced the potential use of sports biomechanics research (such as quantification of knee joint ligament forces from a dynamic model and optimising gymnastics performance through simulation of in-flight movements). Biomechanics research may also play an integral role in reducing the incidence and severity of sporting injuries (such as identification of the causes of back injuries in cricket, and the causes of knee joint injuries in sport). In the following discussion no attempt will be made to reference all papers published in each of these areas because of the enormity of the task. Published and current work from the biomechanics laboratory at the Department of Human Movement and Exercise Science at The University of Western Australia will generally be used to illustrate the scope of biomechanics research within that institution.